2009
DOI: 10.1111/j.1365-3121.2008.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas hazard assessment at the Monticchio crater lakes of Mt. Vulture, a volcano in Southern Italy

Abstract: Geochemical investigations have shown that there is a considerable inflow of gas into both crater lakes of Monticchio, Southern Italy. These lakes are located in two maars that formed 140 000 years ago during Mt. Vulture volcano’s last eruptive activity. Isotopic analyses suggest that CO2 and helium are of magmatic origin; the latter displays 3He/4He isotope ratios similar to those measured in olivines of the maar ejecta. In spite of the fact that the amount of dissolved gases in the water is less than that fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 19 publications
(32 reference statements)
2
51
0
Order By: Relevance
“…Vulture groundwater has been the subject of study by Barbieri and Morotti (2003), Gambardella et al (2006), Paternoster et al (2008) and Caracausi et al (2009). On the basis of Sr isotopic analyses, Barbieri and Morotti (2003) suggested that the chemical composition for most springs is likely to depend on their interaction with volcanic rocks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vulture groundwater has been the subject of study by Barbieri and Morotti (2003), Gambardella et al (2006), Paternoster et al (2008) and Caracausi et al (2009). On the basis of Sr isotopic analyses, Barbieri and Morotti (2003) suggested that the chemical composition for most springs is likely to depend on their interaction with volcanic rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Vulture hydrological basin is one of the more important in Southern Italy and the main Italian reservoir of effervescent-mineral waters that are pumped for drinking and irrigation purposes. It is characterized by the presence of numerous CO 2 -rich mineral springs and wells, and the two volcanic maars-called "Laghi di Monticchio"-inside the caldera (Paternoster, 2005;Gambardella et al, 2006;Caracausi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on the volcanic lakes is now available from the VOLADA (2013) database (https://vhub.org/resources/2822). Although Lakes Monoun and Nyos in Cameroon became notoriously famous because of the gas disasters in the mid-1980s, other CO 2 -rich volcanic lakes exist in the world, e.g., Lake Kivu (Democratic Republic of the Congo and Rwanda, see below for references), Laacher See (Germany) (Aeschbach-Hertig et al, 1996), Lake Van (Anatolia in eastern Turkey) (Kipfer et al, 1994), Lago Albano and the two Monticchio lakes (Italy) (Anzidei et al, 2008;Caracausi et al, 2009), Laguna Hule and Rio Cuarto (Costa Rica) (Alvarado et al, 2011), and Lac Pavin (France) (Aeschbach-Hertig et al, 1999).…”
Section: Other Co 2 -Rich Volcanic Lakes In the Worldmentioning
confidence: 99%
“…limnic eruption , cf. Sigurdsson et al 1987 ;Schmid et al 2005 ;Caracausi et al 2009 ;Mott and Woods 2010 ).…”
Section: Introductionmentioning
confidence: 99%